Pemberdayaan Perempuan Di Desa Gunungsari Melalui Deteksi Dan Stimulasi Tumbuh Kembang Anak - Apsari, Duhita Dyah; Mansur, Herawati; Widyana, Erni Dwi; Kusmiwiyati, Ari (LPPM IST AKPRIND Yogyakarta, 2021)
Gunungsari is a village in Batu City, East Java, densely populated area but the status of education, health and the participation of women in health education programs still needs to be improved and empowered. One of health problems found in Gunungsari is the lack of knowledge about children’s growth dan development. The results of the assessment at Gunungsari in 2019 were found 54.8% of mothers never received information about children’s growth and development, so we thought that people especially mothers in Gunungsari needs some knowledges about children’s growth and development. The method used was socialization and education about child growth and development, training and mentoring for KPSP examinations for 28 kindergarten teachers. The purpose to increase the women empowerment by increase the knowledge and skills of kindergarten teachers on the importance of children’s growth and development. The knowledge improvement were assessed from the pretest and posttest. The average score obtained by 28 kindergarten teachers before the events were only 53.9 and increased to 91.7 after community events, they also obtained skill of examination with KPSP. The evaluation was seen after approximately 2 months, showed that 28 kindergarten teachers who were also Posyandu cadres have implemented growth and development examinations with KPSP in kindergarten and Posyandu, but due to the COVID-19 pandemic, their activities could not be carried out optimally. Based on the results, it can be concluded that there was increasing growth in the knowledges and skills of kindergarten teachers about children’s growth and development and its examinations with KPSP.